Biomechanics of medial meniscus tears in the context of pain: a finite element analysis - Daszkiewicz, Karol; Łuczkiewicz, Piotr (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionMeniscal tears represent the most common knee pathology and may be associated with pain. Meniscal pain is caused by direct mechanical stimulation of nociceptors located in the outer, vascular part of the meniscus. Due to difficulties in selecting the optimal surgical treatment, the aim of the study was to analyze the influence of meniscal tears on the stress state in the context of meniscal pain.MethodsRadial, oblique, longitudinal and horizontal tears involving up to 90% of the width of the medial meniscus were modelled using the finite element method. Two types of knee joint loading were simulated: the stance phase of the gait cycle and external tibial rotation combined with compression.ResultsThe highest Tresca equivalent stresses were obtained for the radial tear of the posterior horn. The largest increase in mean shear stress (187%) on the outer surface of the meniscus, relative to the intact meniscus model, was observed for the oblique tear. Neither complete nor partial horizontal tears were associated with changes in shear stress in the innervated part of the meniscus.DiscussionIncreased shear stresses in the innervated part of the meniscus, which may result in pain, were obtained in radial and oblique meniscal tears models. In the longitudinal tear model, instability of the inner part of the meniscus and increased shear stress were observed in the central part of the meniscus and at both ends of the tear.